Emotionally supportive classroom interactions and students' perceptions of their teachers as caring and just. (April 2018) - Gasser, Luciano; Grütter, Jeanine; Buholzer, Alois; Wettstein, Alexander
Abstract: Emotionally supportive classrooms represent an important interactional context for the development of positive perceptions of student–teacher relationships. The present study investigated how students' perceptions of teacher care and justice develop over the upper elementary grades. Moreover, we studied to what degree teachers' observed emotional support predicts changes in perceptions of teacher care and justice in students with and without risks for academic failure. The study consisted of 1209 upper elementary grade students who were followed from grade five (T1) to grade six (T2, 1009 students). Multilevel analyses revealed that, over the year, student perceptions of their teacher as caring decreased in classrooms with low-quality teacher-student interactions in the emotional domain. Moreover, high emotional support from teachers protected students with high academic disengagement from developing negative perceptions of teacher justice. These results suggest a protective function of teacher's emotional support. Highlights: Students' perception of teacher care and justice are key aspects of student-teacher relationships. 1209 students from Switzerland were followed from the 5th to the 6th grade. Students' perceptions of teacher care decreased during the upper elementary grades. Students' academic risks negatively related to perceptions of teacher care and justice. Teachers' emotional support buffered these negative effects on students' perceptions of teacher care and justice.